- Pelatihan empati untuk mengurangi intensitas perilaku bullying pada remaja - Makkiyatur Rahmah (Psychological Journal: Science and Practice, 2021)
Cases of bullying that happens in school are conducted indirectly, whether its verbally, or even physically. One of the triggers of a student behaved bullying is the low empathy. The purpose of this research is to examining whether increasing empathy training can reduce the intensity of bullying behavior. This research used an experimental quantitative approach with a pretest-posttest control group design and quasi experimental design with subjects of 6 students for the experimental group and 6 students for the control group. This research was conducted at one school in the Malang. This instrument used Olweus Bullying Scale and Basic Empathy Training with data analysis using the Wilcoxon test and the mann-withney test. The result of the Wilcoxon test indicates there is a difference in empathy after empathy training with a sig 0.028 and bullying behavior obtained a sig 0.028. This point directly proportional to the results of the mann-whitney bullying behavior in the two groups sig 0.004. Based on these results it indicates empathy training significantly reducing the intensity of bullying behavior.